CIAT forage hybrids and varieties released globally for more productive and resilient livestock systems - CGIAR Research Program on Livestock (2021)
New cultivars originating from the CIAT gene bank (cvv. Sabanera, Caporal and Centauro) and the CIAT Urochloa breeding program (cvv. Mulato II, Cayman, Cobra, Camello) were released in Colombia, Kenya and South East Asia. These new cultivars are highly versatile regarding use (e.g. grazing or cut-and-carry systems) and adaptation (tropical, subtropical, transition zones). They represent opportunities to improve livestock system productivity and resilience through incorporating more forage options that minimize the risk of shortages of feed supplies.